The long-term psychosocial impact of corrective surgery for adults with strabismus. Issue 4 (14th February 2013) - Jackson, Sue; Morris, Marianne; Gleeson, Kathryn
Abstract : Background/Aim: Long-term assessments of the impact of strabismus surgery in adults are rare and very limited in focus. Consequently, this study was designed to consider the psychosocial status of adults a minimum of 1 year after surgery. Methods: A repeated measures design, 25 participants were seen at 6-week pre-operative (T1), 3-month (T2) and 18-month (T3) post-operative appointments. Participants completed a battery of psychological scales comprising: Hospital Anxiety and Depression scale, the World Health Organisation Quality of Life assessment (short form), the Derriford Appearance Scale, and visual analogue scales to measure the impact of strabismus and its treatment on psychological adjustment and daily functioning. Results: At T2, all scores on all study measures had significantly improved. At T3, some study measures were showing continued improvement: World Health Organisation Quality of Life Assessment - short form (WHOQoL-Bref) social and environment domains; DAS-24; VAS scales for coping, postoperative satisfaction, strabismus noticeability and strabismus severity. A one-way Analysis of Variance (ANOVA) showed significant effects across time for DAS-24 and all VAS scales. Post hoc tests indicated that significant changes occurred between T1 and T2 and between T1 and T3. Conclusions: This study suggests that adjustment is a long-term process with improvements on some study measures being greater at 18 months than at 3 months postoperatively raising the possibility that some psychosocial goals are more appropriately measured in the longer term.